Semantic and Syntactic Interoperability Issues in the Context of SDI - Chojka, Agnieszka (Geomatics and Environmental Engineering, 2020)
Interoperability is one of the core concepts of Spatial Data Infrastructure due to the fact that exchange and access to spatial data is the foremost aim of any SDI. These issues are closely related to the concept of application schema that plays a significant role in interchanging spatial data and information across SDI. It is the basis of a successful data interchange between two systems as it defines the possible content and structure of data, thus it covers both semantic and syntactic interoperability. These matters also appear in a couple of questions concerning SDI including, among others, a model‑driven approach and data specifications. Spatial data exchange through SDI involves UML and GML application schemas that comprise semantic and syntactic interoperability respectively. However, working out accurate and correct application schemas may be a challenge. Moreover, their faultiness or complexity may influence the ability to valid data interchange. The principal subject of this paper is to present the concept of interoperability in SDI, especially semantic and syntactic, as well as to discuss the role of UML and GML application schemas during the interoperable exchange of spatial data over SDI. Considerations were conducted focusing on the European SDI and the National SDI in Poland.